Outline of Tertiary Coal Basins of Indonesia - R.P. Koesoemadinata (Berita Sedimentologi, 2002)
Base on crustal composition and plate tectonics the Indonesian Archipelago can subdivided into three distinct tectonic regions, namely: Western Indonesia, Central Indonesia, and Eastern Indonesia. Western Indonesia consists of the Sunda shelf belonging to the Asian continent and its associated active margin continental island arcs and passive margins as well as intracontinental tectonic features, such as sutures. Central Indonesia consists of an assortment of sliding and colliding continental fragments or micro-continents, mainly detached from the Australian continent amids oceanic platelets of various ages and associated volcanic island arcs. Eastern Indonesia consists of the Arafura Shelf belonging to the Australian continent and its associated continental margin features.Previously Tertiary coal deposits in Western Indonesia were classified as Paleogene and Neogene coals. Recent knowledge indicates that Tertiary coals was deposited during three distinct tectonic episodes: 1) Syn-rift depositional phase (Eocene-Oligocene), 2) Post-rift transgression phase (Late Eocene to Early Miocene), and 3) Syn-orogenic regressive phase (Mid-Miocene to Plio-Pleistocene). These episodes do not occur at the same time throughout western Indonesia, but varies from basin to basin.Syn-rift coal was deposited in active rift basin and associated valley-fill sediments in fluviatile to lacustrine environment. Coal deposited in this environment tends to be lenticular and limited areal extent, with high calorific values (~7000 Kcal/kg), low moisture content and low sulphur content. This type of coal is represented by Sawahlunto Formation in Ombilin basin, Central Sumatra.Post-rift transgressive coal was deposited on a stable shell environment, during a tectonic quiesence in Late Eocene to Early Miocene time. Examples of this coal is given from Central Sumatra basin (Early Miocene), and especially represented by Senakin coal in the Eocene Lower Tanjung Formation in the Barito basin and in the Pasir-Asem-asem basin. Coal seams deposited in this environment tends to be thin but laterally continuous and persistent, with high calorific values, variable to high sulphur content.Syn-orogenic regressive coal deposition took place in mid-Miocene to Plio-Pleistocene time in response to uplifts adjacent to various types of basins in which the coal was deposited. In Java and Sumatra these are the back-arc and fore-arc basins, as the result of the Indian oceanic plate subduction beneath the Asian continent forming an island arc environment. Coal was deposited in a prograding deltaic sequence both in the fore-arc (Bengkulu basin) and back-arc basin South Sumatra or Palembang basin in response to the uplift of the magmatic arc. In South-east Kalimantan syn-orogenic coal was deposited in the regressive sequence of the Miocene Warukin Formation (Warukin Coal) in response to uplift of the Meratus Range suture on the related adjacent Barito and Asem-asem/Pasir basins. In East Kalimantan syn-orogenic coal was deposited in prograding deltas developed at the passive margin associated with the opening of Makassar Strait (Lower Kuteri and Tarakan basins), and regression took place in response to the uplift of the Kuching zone towards the west. An example of this syn-orogenic coal is the Pinang coala in the Balikpapan Formation. Coal in the syn-orogenic regressive phase tends to develop thick but variable seams, rather low calorific values (~5000 kcal/kg), high moisture content, and low sulphur content.In Central Indonesia region, only SW Sulawesi, a continental fragment belonging to the Sunda shelf, shows significant coal deposits. Syn-rift, post-rift transgressive and syn-orogenic coal can be distinguished, such as the syn-rift coal at Tondongkura.Eastern Indonesia is dominated by the island of Irian Jaya/Papua, which shows the same tectono-stratigraphic development as on the Australian mainland. The Tertiary sequence is mainly developed as carbonates. Clastics were deposited in only in Plio-Pleistocene time in response to uplifts related to collision of the Australian continent with island arcs systems, and to lateral displacement of continental fragments. Lignites are known in the resulting syn-orogenic basins, such as the foreland basins of the Central Irian Jaya Mts range (Akimeugah and Iwur basins), the Meervlakte or Mamberamo basin in North Itian Jaya, the Bintuni basin associated with the Lengguru foldbelt, and the Salawati basin related to wrenching of the Sorong Fault. However, significant coal occurrences are known in Bintuni basin, which at present is still an enigma.